Impact of slope and pipe diameter on flush plume design - Joseph P. Harner; John F. Smith; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2007)
Manning's equation provides a method to evaluate the flow characteristics of a flush plume system used to move a diluted, sandladen manure stream from a freestall building to sand or solid separation equipment. Evaluation of a 16, 18, and 24-inch plume showed pipe slope is critical in maintaining a 5 feet per second water velocity through the pipe. A 24 inch or larger plume placed on a 0.5% slope is able to obtain water velocity of 5 feet per second if the pump capacity exceeds 3,600 gpm. The flow velocity never reached or exceeded 5 feet per second in a 16- or 18-inch pipe placed on a 0.5% slope, regardless of the pump capacity. A 16-, 18- or 24-inch pipe laid on a 1% slope could obtain a water velocity of 5 feet per second if the pump capacity exceeded 1,500 gallons/minute.; Dairy Day, 2007, Kansas State University, Manhattan, KS, 2007; Dairy Research, 2007 is known as Dairy Day, 2007
Keywords: Dairy Day; 2007; Kansas Agricultural Experiment Station contribution; no. 08-127-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 984; Dairy; Sand; Plume; Flush; Sand sparation